The Impact of Customer Satisfaction on Word-of-Mouth: Conventional Banks of Malaysia Investigated - Jan, Muhammad Tahir; Abdullah, Kalthom; Shafiq, Ali (Institute of Information System & Research Center, 2013)
Purpose – The main purpose of this paper is to test the impact of customer satisfaction on word-of-mouth in the banking industry of Malaysia. Design/methodology/approach – A framework was developed based on the extensive review of literature, with two variables – customer satisfaction and word-of-mouth. The causal relationship envisaged was tested using Structural Equation Modelling. For this purpose a self-administered structured questionnaire was distributed among 500 customers registered with different banks operating in Malaysia. Out of the total 500 distributed questionnaires 407 were finally selected for data analyses. SPSS and AMOS software programmes were used to analyse data. Data analyses encompass descriptive analyses, reliability tests, exploratory factor analysis (EFA), confirmatory factor analysis (CFA), and full fledge structural modelling. Findings – The results reveal that customer satisfaction has a significant positive impact on word-of-mouth. Data resulted in acceptably high reliability during the reliability tests. Exploratory factor analysis for customer satisfaction resulted in 3 dimensions which were further converged into 2 dimensions during confirmatory factor analysis. Measurement models resulted in good fit giving a green signal for testing causal relationship and full structural modelling. The results of full fledge structural model indicated good fit with the data. In this case, a normed chi-square (χ²/df) of 3.087, comparative fit index (CFI) of 0.954, and root mean square error of approximation (RMSEA) of 0.045 indicate the same. Practical implications – A high positive significant impact (0.825) of customer satisfaction on word-of-mouth clearly indicates that it is imperative for banking sector to enhance customer satisfaction. This is due to the inevitable growth of information technology, instant popularity of websites such as Facebook, Twitter, YouTube, and Wikipedia which have given liberty to customers in spreading their positive or negative feedback quickly and conveniently. Policy makers of service industry in general and financial service industry in particular may benefit from the findings of this study. Originality/value – Importance of word-of-mouth is not new to the organisations. This research is a unique attempt, using structural equation modelling (SEM), to investigate the impact of customer satisfaction on word-of-mouth in the banking industry of Malaysia.